Production of Bioethanol from Oil Palm Empty Fruit Bunch - Cheng, C. K.; Hajar, H. Hani; Ku Syahidah, Ku Ismail (2007)
Several methods have been identified to produce bioethanol. Bioethanol can be synthesized from cellulose and hemicelluloses that originate from the many sources of biomass current studies focused on the production of bioethanol from oil palm waste using saccaromyces cerevisie as fermentation agent.